2011
DOI: 10.1111/j.1574-6941.2011.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal gut microbiota of adolescent children is different from that of adults

Abstract: Human intestinal microbiota plays a number of important roles in human health and is also implicated in several gastrointestinal disorders. Though the diversity of human gut microbiota in adults and in young children has been examined, few reports of microbiota composition are available for adolescents. In this work we used Microbiota Array for high-throughput analysis of distal gut microbiota in adolescent children 11-18 years of age. Samples obtained from healthy adults were used for comparison. Adolescent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
213
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(228 citation statements)
references
References 38 publications
9
213
3
3
Order By: Relevance
“…Studies in newborn mice and in human infants have suggested that bacterial communities in the gut are initially unstable but become more stable in early childhood and develop more modestly throughout adulthood [106,107]. However, this may not be the case with the gut mycobiota.…”
Section: Fungi Inhabiting the Gutmentioning
confidence: 95%
“…Studies in newborn mice and in human infants have suggested that bacterial communities in the gut are initially unstable but become more stable in early childhood and develop more modestly throughout adulthood [106,107]. However, this may not be the case with the gut mycobiota.…”
Section: Fungi Inhabiting the Gutmentioning
confidence: 95%
“…Although relatively stable, the gut microbiota is affected by age, gender, geography, diet, and environmental factors, such as exposure to antibiotics, especially in children and newborns (Backhed et al, 2005;Agans et al, 2011;Vael et al, 2011;Grzeskowiak et al, 2012;Markle et al, 2013;Trasande et al, 2013). There are numerous studies related to gut microbiota changes (dysbiosis) caused by antibiotics and probiotics, including weight modifications in humans and animals (Ley et al, 2006;Turnbaugh et al, 2008;Xu et al, 2012;Bibiloni, Pons, Tur, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…90,91 Specifically MDA, a product derived from the oxidation of PUFAs, was shown to be increased in NASH patients. [91][92][93] In line, higher antibody titers of MDA-derived adducts were associated with increased severity of lobular inflammation and a 13-fold increased risk of developing NASH, indicated by an NAFLD activity score of ≥5 in a biopsy-proven pediatric NASH cohort. 94 Additionally, other FA-derived oxidation products have been associated with NASH.…”
Section: Oxidized Lipids In Human Nashmentioning
confidence: 74%
“…91,92 Moreover, lysosomal dysfunction impairs autophagy, a process that mediates the self-degradation of cellular components. 93 As multiple studies have shown the tight link between autophagy and inflammation, [94][95][96] lysosomal dysfunction can affect the inflammatory response by impairing autophagy. Altogether, these findings present a clear relation between lipid metabolism, lysosomes and inflammation.…”
Section: Lysosomal Function and Its Role In Lipid Metabolism And Inflmentioning
confidence: 99%
See 1 more Smart Citation